Management of Risk Management on Banking Financial Performance - Rahma Dewi, Wulan (Jurnal Keuangan dan Perbankan (KEBAN), 2021)
Risk management is very important for companies. The purpose of this study is to examine and analyze the impact of credit risk, market risk, operating efficiency, capital, and liquidity on bank financial performance. This research uses a quantitative research design. The data used in this study is based on private banks listed on the Indonesia Stock Exchange (IDX) for the next three years. The type of data is secondary data. Technical analysis using multiple linear regression. The results show that market risk and operating efficiency have a significant effect on the financial performance of the bank. Meanwhile, credit risk, capital, and liquidity have no significant effect on the bank's financial performance